Influence of Geometric and Setup Parameters of the Arrangement of Working Tools on Agrotechnical and Power Characteristics - S. A. Sidorov; Ya. P. Lobachevskiy; D. A. Mironov; A. S. Zolotarev (Сельскохозяйственные машины и технологии)
The paper contains the analysis results of the influence of geometric and setup parameters of the plow working tools on agrotechnical indicators and traction resistance of a plow. (Research purpose) To determine the agrotechnical indicators of tillage quality depending on the type of a plow moldboard and determine the optimal moldboard for loamy soils. (Materials and methods) Agrotechnical indicators included crumbling, soil layer turnover, and the incorporation (embedding) degree of plant residues. More intensive lumpiness is observed as the content of clay particles increases. The angle of plow body setup relative to the furrow walls is changed using the middle bolts securing the plow body rack of the frame and installing additional washers on one of the two remaining bolted joints. For experiments on the influence of the inclination angle of the plow-bottom surface relative to the furrow wall, the plow bodies were located at angles of 30 to 55 degrees. (Results and discussion) It has been established that at angles of 30-35 degrees, the diameter of clods increases to values exceeding the permissible norm by 10-20 percent. An increase in the angle of more than 45 degrees reduced the diameter of clods to 10-30 millimeters. With an increase in angle to 50-55 degrees, shearing chips changed into shifting chips. The authors determined traction resistance of plows with various types of moldboards and identified the results of analytical calculations and experimental data in field trials using a dynamometer. Traction resistance of the plow decreases as cylinder moldboards are substituted with screw (auger-type) ones. (Conclusions) It has been determined that as the angle of plow body setup relative to the furrow walls increases, the size of soil fragments decrease, and shearing chips change into shifting chips. It has been proved that general-purpose and half-screw moldboards demonstrate the best agrotechnical indicators on loamy soils